The Creativity of Physical Education Teachers, Sports, and Health - Ikhwan Abduh; Andi Saparia; Jumain Jumain; Ziulhaq Ziulhaq; Moh Usba (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. Creativity is a crucial attribute required in various professions, and its significance is particularly evident in the field of education, including teaching. The ability to innovate and think creatively is essential for educators to effectively adapt to and address the ever-evolving landscape of advancements and challenges. This research study was conducted with the specific objective of evaluating and quantifying the degree of originality demonstrated by physical education teachers. The assessment encompassed seven distinct indicators, providing a comprehensive analysis of the teachers' creative abilities within the context of their profession. Methods and Materials. The study used a descriptive research design, involving systematic observation of phenomena and forming conclusions based on the observations. The research was conducted in two sub-districts, Taweli, and North Palu, covering a total of 29 schools. All 35 Physical Education teachers in the area were included in the study using total sampling. Data was collected through a questionnaire and analyzed using descriptive and frequency distribution analysis to determine percentage scores within the sample. Result. The research findings have been sorted by gender, employment status, and certification status. The study found that women show higher levels of creativity compared to men, especially in the highly creative category. 9% of women demonstrated this level of creativity, while only 6% of men did. When looking at employment status, civil servants are more likely to be classified as very creative, with 11% falling into this category compared to 3% for honorary positions. In terms of certification status, 11% of those certified fall into the very creative category, while for the non-certified category, the proportion is 3%. Conclusion. Upon examination of the research data, it was found that among the 35 samples, 5 (14%) were labeled as extremely creative, 5 (14%) as creative, 14 (40%) as not creative, and 11 (31%) as highly uncreative. This suggests that there is a low level of creativity among PJOK teachers, as indicated by the largest percentage within this group. However, it is important to note that when combining the percentages of highly creative and creative, the overall figure remains substantial at 28%.